Analysis of Accounting Information System on Cash Receiving Function (Case Study on CV. Abers Jaya Mandiri Tanjung Selor) - Saputri, *Novitasari Agus; Ramdhani, Andi; Zubaidah, Siti (Universitas Syiah Kuala, 2022)
This study aims to explain the accounting information system on the cash receipts function carried out by CV. Abers Jaya Mandiri Tanjung Selor, this research is a qualitative descriptive research which is a study to investigate, analyze, explain, and describe the quality of social influence in order to determine the application of accounting information systems to the cash receipts function of CV. Abers Jaya Mandiri Tanjung Selor. In this study, the research results obtained by researchers in the input section are seen from some of the documents used, there is no authority from the company, other than that the form belongs to CV. Abers Jaya Mandiri Tanjung Selor not all have detailed serial numbers. In the process section, the company does not carry out inventory recording and bank reconciliation, besides that the procedure for receiving cash from credit sales is not adequate with the procedure for granting credit and in the financial statements as the company's output still has shortcomings, namely the financial statements do not have information and explanations, so for the layman difficult to understand from the reports issued by the company. This study aims to explain the accounting information system on the cash receipts function carried out by CV. Abers Jaya Mandiri Tanjung Selor, this research is a qualitative descriptive research which is a study to investigate, analyze, explain, and describe the quality of social influence in order to determine the application of accounting information systems to the cash receipts function of CV. Abers Jaya Mandiri Tanjung Selor. In this study, the research results obtained by researchers in the input section are seen from some of the documents used there is no authority from the company. In the process section the company does not carry out inventory recording and bank reconciliation and in the financial statements as output the company still has shortcomings, namely financial statements has no description and explanation.